Kualitas Pelayanan, Pengalaman, Kepuasan, dan Perilaku Keluhan Terhadap Loyalitas Pelanggan - Rojuaniah, Rojuaniah; Savira, Karin Putri; Syah, Tantri Yanuar Rahmat; Havidz, Ikramina Larasati Hazrati; Winanta, Tang Tatang (Universitas Batanghari Jambi, 2024)
The rapid development of online business in Indonesia is increasing because of the character of people in indonesia who always want easy and practical shopping.most of the online businesses themselves use freight forwarding services for export and import activities. This leads to intense competition in the freight forwarding service industry, the purpose of this study to determine the effect of quality of service, customer experience, customer satisfaction or even customer complaint behavior on customer loyalty in the freight forwarding service industry companies.This study was designed using purposive sampling method involving 105 populations of freight forwarder customers. The Data were analyzed using structural Equation Model (SEM) PLS . the results of this study are service quality has a positive and significant effect on customer satisfaction and customer loyalty, customer experience has a positive and significant effect on customer satisfaction and customer loyalty, customer satisfaction has a positive and significant effect on customer loyalty, customer complaint behavior has a negative and significant effect on customer loyalty. In this study can be input to the freight forwarding service industry in order to be fix or improve the quality and good experience for customers so that customers feel satisfied and there are no complaints given, because if customers complain constantly without a solution and no change in the company then there is no customer loyalty.